Cambios en la función vascular de hombres saludables, después de ejercicio físico prolongado y vigoroso (2010)
The effect of prolonged and strenuous exercise on endothelial function in 9 non-elite runners was researched determining the endothelium-dependent function of the femoral artery (EDF-FA). We realized that prolonged and vigorous exercise is associated with lower EDF-FA, with non significant trend toward recovery from 24 hours to 7 days after the race. Studies with more participants are required to determine the impact of prolonged and vigorous exercise on endothelial function